METODE PEMBELAJARAN SASTRA PADA MATA PELAJARAN BAHASA INDONESIA - Al-afandi Al-afandi (Guru Tua : Jurnal Pendidikan dan Pembelajaran, 2022)
This paper aims to introduce the method of learning literature in Indonesian subjects. Literary material, especially poetry appreciation, is often a problem for teachers and students. To overcome this problem, one of the solutions offered by the author is in the form of a method that is considered to be able to solve problems in literary learning, especially in poetry appreciation. Some of the literary teaching methods applied include the lecture and question and answer method, discussion, audio-visual and content analysis. The implementation steps taken by teachers and students are (a) choosing poetry literary texts (b) choosing learning media, (c) analyzing poetry literary texts together. (d) form groups of students. (e) student work assignments. (f) the percentage of students in front of the class using the media. (g) discussion and question and answer